Measuring employee engagement in the Institut Tadbiran Awam Negara (INTAN) Kampus Wilayah Selatan / Nur Diyana Noor Sham - Noor Sham, Nur Diyana (Faculty of Business and Management, 2018)
The purpose of this research is to determine the antecedents of employee engagement such as reward/recognition, role clarity and teamwork against workers at Institut Tadbiran Awam Negara (INTAN) Kampus Wilayah Selatan. Institut Tadbiran Awam Negara (INTAN) Kampus Wilayah Selatan is a training center located under the Public Service Department. INTAN has it main campus which located at Bukit Kiara, Kuala Lumpur. Besides, INTAN also has several branch campuses. Which is INTAN Kampus Wilayah Tengah (INTENGAH) at Jalan Elmu, Kuala Lumpur; INTAN Kampus Wilayah Utara (INTURA) at Sungai Petani, Kedah; INTAN Kampus Wilayah Selatan (IKWAS) at Kluang, Johor; INTAN Kampus Wilayah Timur (INTIM) at Kemaman, Terengganu; INTAN Kampus Sabah at Tuaran, Sabah; and INTAN Kampus Sarawak at Kota Samarahan, Sarawak. This research focus more to workers at INTAN Kampus Wilayah Selatan. INTAN Kampus Wilayah Selatan has around 69 workers. All the workers in INTAN Kampus Wilayah Selatan were appointed by Jabatan Perkhidmatan Awam (JPA). This research use descriptive study to determine employee engagement at INTAN Kampus Wilayah Selatan. The targeted population is 69 of the workers at INTAN Kampus Wilayah Selatan and the sample size in this research is 59 respondents out of 69 workers. All of the respondents is selected through simple random sampling techniques. Questionnaires which is primary data were used in this research to collect all the data. In this research all the data that have been collected were analyze by using Reliability analysis, Frequency distribution analysis, Descriptive statistical analysis, Pearson’s correlation coefficient analysis, Multiple regression analysis and Hypothesis testing. Nevertheless, the result of this research indicates that the antecedents of employee engagement is reward/recognition, role clarity and teamwork. All the antecedents have positive relationship with employee engagement.